Parametric model of servo-hydraulic actuator coupled with a nonlinear system: Experimental validation. (1st May 2018) - Maghareh, Amin; Silva, Christian E.; Dyke, Shirley J.
Highlights: A servo-hydraulic actuator is coupled with nonlinear system. A damage-controlled nonlinear device is designed, fabricated and tested. A dynamical model for the servo-hydraulic actuator is experimentally validated. Time-domain comparisons and errors associated with the experiments are provided. Abstract: Hydraulic actuators play a key role in experimental structural dynamics. In a previous study, a physics-based model for a servo-hydraulic actuator coupled with a nonlinear physical system was developed. Later, this dynamical model was transformed into controllable canonical form for position tracking control purposes. For this study, a nonlinear device is designed and fabricated to exhibit various nonlinear force-displacement profiles depending on the initial condition and the type of materials used as replaceable coupons. Using this nonlinear system, the controllable canonical dynamical model is experimentally validated for a servo-hydraulic actuator coupled with a nonlinear physical system.